Superstar Central Bankers - Matthias Neuenkirch; Peter Tillmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The personalities of central bankers moved center stage during the recent financial crisis. Some central bankers even gained "superstar" status. In this paper, we evaluate the pivotal role of superstar central bankers by assessing the difference an outstanding governor makes to economic performance. We employ school grades given to central bankers by the financial press. A superstar central banker is one receiving the top grade. In a probit estimation we first relate the grades to measures of economic performance, institutional features, and personal characteristics. We then employ a nearest neighbor matching approach to identify the central bankers which are closest to those receiving the top grade and compare the economic performance across both groups. The results suggest that a superstar governor indeed matters: a top-graded central banker faces a significantly more favorable output-inflation trade-off than his peers.
Keywords: E52; E58; E50; 330